The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1541-0420.2007.00944.x
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Generalized Estimating Equations for the Analysis of Clustered and Longitudinal Data

Abstract: A common and important problem in clustered sampling designs is that the effect of within-cluster exposures (i.e., exposures that vary within clusters) on outcome may be confounded by both measured and unmeasured cluster-level factors (i.e., measurements that do not vary within clusters). When some of these are ill/not accounted for, estimation of this effect through population-averaged models or random-effects models may introduce bias. We accommodate this by developing a general theory for the analysis of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 17 publications
(48 reference statements)
1
83
0
Order By: Relevance
“…How big a problem is this? Brumback et al (2010Brumback et al ( :1651 found that, in running simulations, "it was difficult to find an example in which the problem is severe" (see also Goetgeluk and Vansteelandt 2008). In a later paper, however, Brumback et al (2013) did identify one such example, but only with properties unlikely to be found in real life data (Allison 2014)-x i and i very highly correlated, and few observations per level-2 entity.…”
Section: Generalising the Re Model: Binary And Count Dependent Variablesmentioning
confidence: 99%
“…How big a problem is this? Brumback et al (2010Brumback et al ( :1651 found that, in running simulations, "it was difficult to find an example in which the problem is severe" (see also Goetgeluk and Vansteelandt 2008). In a later paper, however, Brumback et al (2013) did identify one such example, but only with properties unlikely to be found in real life data (Allison 2014)-x i and i very highly correlated, and few observations per level-2 entity.…”
Section: Generalising the Re Model: Binary And Count Dependent Variablesmentioning
confidence: 99%
“…We tested the association between medication use and the test scores using a conditional generalized estimation equation (CGEE), conditioning on the individual patient. 29,30 The analyses were performed with and without the adjustment of time-varying confounders including age and the number of previous tests. Because each individual serves as his or her own control in this design, all the time-invariant confounders were implicitly adjusted for.…”
Section: Discussionmentioning
confidence: 99%
“…approach is expected when there are no random slopes [37]. Lastly, the joint modelling approach performs rather well in terms of bias, except for the estimators obtained under the third simulation setting (where assumption (vi) is violated) for the larger sample size, where we find significant bias for all three parameters.…”
Section: Parameter Estimatesmentioning
confidence: 66%
“…The question of whether or not the approach of Imai et al [11] yields unbiased estimators for the direct and indirect effects in the presence of unmeasured subject-level confounders in non-linear settings remains to be explored. However, separating within-and between-effects in mixed models with log-or logit-links may yield inconsistent within-subject effects in the presence of unmeasured subject-specific confounders [37]. We conjecture that the mediation package approach in the multilevel setting may require assumptions that are too stringent, even if centred predictors were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation